Microgeração de energia elétrica (Abaixo de 100 kW) utilizando turbina Tesla modificada - César Batista, Júlio; De Carvalho Júnior, João Andrade [UNESP] (My University, 2010)
An economical electricity generating system is developed, i.e., a boiler and turbine with a capacity ≤ 100 kw, to occupy a niche market where the existing steam systems are not economically viable. A Tesla turbine is used. It has been modified to provide greater torque, outperforming the deficiency inherent in the original Tesla turbine. It can operate with saturated steam produced by a boiler heated by biomass, gas, biodiesel, etc. The microgenerator consumes locally available fuel and can bring energy to millions of rural living Brazilians, where some kind of biomass is abundant. The Tesla turbine is compact, has no moving parts, and has endless application possibilities. A prototype system is also created to produce electricity with a boiler and generator.
Microgeneration of electricity (Below 100 kW) using modified Tesla turbine
Keywords: Microgeneration; Steam turbine; Tesla turbine